2020
DOI: 10.1177/0308022620939859
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between executive functions and occupational performance of children with medulloblastoma

Abstract: Introduction This study examines executive functions and occupational performances of children with medulloblastoma and children with typical development. The aim was to compare the executive function and occupational performance levels of children with medulloblastoma and children with typical development and to investigate the relationship between the executive function and occupational performance levels of children with medulloblastoma. Method Parents of 105 children (6–12 years) completed the Childhood Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Unlike the baseline phase, at the end of the intervention phase, PND related to SCWT (interference score) and WCST (perspective error) was more than 50% which may be an indicator of the effectiveness of OPC and 4QM interventions on the executive function skills. Our results are similar to findings from studies indicating that there is a significant correlation between executive function skills and occupational performance areas [ 14 , 65 , 66 ]. Therefore, using a top-down approach, the child was helped to perform daily life activities independently and improved executive function skills such as cognitive flexibility, attention, response inhibition, automation, semantic memory, and self-control based on the SCWT and WCST components.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the baseline phase, at the end of the intervention phase, PND related to SCWT (interference score) and WCST (perspective error) was more than 50% which may be an indicator of the effectiveness of OPC and 4QM interventions on the executive function skills. Our results are similar to findings from studies indicating that there is a significant correlation between executive function skills and occupational performance areas [ 14 , 65 , 66 ]. Therefore, using a top-down approach, the child was helped to perform daily life activities independently and improved executive function skills such as cognitive flexibility, attention, response inhibition, automation, semantic memory, and self-control based on the SCWT and WCST components.…”
Section: Discussionsupporting
confidence: 91%
“…Reducing the deterioration of mood productivity (school, and routine tasks), play and leisure time (QOL and social interactions) [50]. Various studies in the literature show that children with cancer have poor OP [50][51][52]. During the COVID-19 pandemic period, although all individuals around the world take measures such as social distancing, wearing masks, staying at home as much as possible, higher-level measures such as "excessive social distancing" has been recommended especially for this group, as they are in the high-risk group [53].…”
mentioning
confidence: 99%
“…11 These factors limit patients’ ability to exercise and their processing skills, thereby affecting their performance of daily tasks. 9 Önal and Huri 55 revealed that patients with medulloblastoma exhibit poorer executive function and occupational performance than do patients without medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%